Workplace development and learning in elder care – the importance of a fertile soil and the trouble of project implementation - Westerberg, Kristina (Outlines. Critical Practice Studies, 2004)
Workplace learning and competence development in work are frequently used concepts. A wide spread notion is that societal, institutional, and organizational changes require the development of knowledge, methods and strategies for learning at workplaces, in both public and private enterprises. In research on learning and competence development at work, the organizational learning and development as well as individual accomplishments are investigated from various perspectives and in different contexts. The theoretical base for research projects can, accordingly, be focused at a number of organizational and system levels. This paper describes a research project called "Workplace development and learning in elder care" in which learning and knowledge were key issues and where Activity Theory was used as the theoretical base. The project was joint project between two research and development field units. These were UFFE, a municipal social services’ field research unit, and Äldrecentrum Västerbotten, a county council field research unit which aims to serve the interests of the elderly. The project was launched in the fall of 2000 and ended in the summer of 2003. I was employed part-time as a research leader at the municipal research unit and became the research leader for this particular project. A number of students, as well as employees from the county council geriatric care services and the municipal elder care participated in the project. The general aims of the project were to: a) investigate the prerequisites for development and learning; b) test and evaluate interventions at a workgroup level; and c) identify the need for new knowledge. The results were expected to be useful for the field research units as well as for the municipal and county eldercare services in their research and development work. I start with a presentation of the theoretical concepts and apply them in order to form a tentative hypothesis on the status of learning and knowledge in elder care. The next section contains a short description of the different parts of the project and the main results are presented. Finally, the results are discussed and related to the conditions and impact of workplace interventions.